IDENTIFICACIÓN DE LAS LIMITANTES DEL COMPORTAMIENTO REPRODUCTIVO Y LA EFICIENCIA DE LA INSEMINACIÓN ARTIFICIAL EN GANADO LECHERO DE LA ZONA DE LIMA - Echevarrìa C., Luisa (2002)
The reproductive performance in seven intensive dairy farms of the Lima region was evaluated. The interval from calving to first service (CFSI) in 552 dairy cows and the interval from calving to conception (CCI) in 249 cows were determined considering the effects of parity (uniparous and multiparous ), breed (Holstein and Brown Swiss ), calving season (G 1-Summer, December to April; G2-Winter, May to August; G3-Spring, September to November) and farm. Overall conception rate and conception rate at first service in two periods (1: 1995-1996; 2: 1997-1998) were analyzed. Heat detection and artificial insemination (Al) efficiency was evaluated in 512 services using progesterone levels and pregnancy diagnosis results. Data was analyzed by GLM using analysis ofvariance and logistic regression. CFSI was 81.1 ± 35 days and CCI was 113 ± 61 days (mean± s.d.). Factors that significantly affected CFSI were parity and calving season. CFSI in uniparous . was 89.9 ± 3.8 days (LS ±SE, n = 148) and in multiparous was 81.3 ± 2.6 days (n = 404, P<0.01). CFSI forGl, G2 and G3 was 87.3 ± 2.7, 68.8 ± 2.8and100.9 ± 5.7 days,respectively (P<0.01). CCI was 117.4±4.6, 95.0±6and 154.6± 12days forGl, G2 andG3,respectively, · with differences between G2 and the other groups (P<0.01). Parity did not affect CCI. lnterval from calving to first ovulation (COI) was 45 ± 19.9 days (n = 65), and was affected by BCS at calving, season of calving and farm (P<O.O 1 ). COI in cows that cal ved in spring was 42.8 ± 2.6 days whereas in cows that calved in summer was 23.2 ± 6.1 days. Cows inseminated in spring were more prone to be inseminated at inappropriate time. Overall conception rate and conception rate at first service were affected by the study period, service number, and origin of semen. Cows that cal ved in the September -April period had the longest intervals and should be included in a special Al scheme for improving their performance.